PENERAPAN METODE WSM PADA FAKTOR PENYEBAB RENDAHNYA MINAT MAHASISWA DALAM BELAJAR BAHASA INGGRIS - Parhusip, Friskila; Hartama, Dedy; Nasution, Zulaini Masruroh (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
English is one of the important components in realizing a quality college and being an international language means the language that will be used when conducting conversations between countries or nations. To realize a quality college, STIKOM Tunas Bangsa began to impose an increase in learning English. However, this was found to be an obstacle, namely the low interest of students in learning English. In this study will be determined the factors that are the main reason for the low interest of students in learning English. Data inputted based on the results of the questionnaire with the STIKOM Tunas Bangsa case study, then processed using the Weighted Sum Model (WSM) method by determining the alternatives to be used as reference in retrieval. decisions, namely, the level of difficulty, the level of understanding, environmental factors, and the role of the lecturer. The test results show that the WSM method is able to produce factors of low student interest in learning English based on the required criteriaKeywords: English Language, Decision Support System, WSM Method, Student Interest.